Answer: 1) Let's simplify step-by-step.
x22(x+y)−y2
Distribute:
=(x22)(x)+(x22)(y)+−y2
=x23+x22y+−y2
Answer:
=x23+x22y−y2
2)Let's simplify step-by-step.
x4+x2y2+y4
There are no like terms.
Answer:
=x4+x2y2+y4
Answer:
![{ax}^{3} + 4ax \\](https://tex.z-dn.net/?f=%20%7Bax%7D%5E%7B3%7D%20%20%2B%204ax%20%5C%5C%20%20)
factorise out a and x :
![{ \boxed{answer{= ax( {x}^{2} + 4) }}}\\ but \: farther \: more : \\ = ax( {x}^{2} + {2}^{2} )](https://tex.z-dn.net/?f=%20%7B%20%5Cboxed%7Banswer%7B%3D%20ax%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%204%29%20%7D%7D%7D%5C%5C%20but%20%5C%3A%20farther%20%5C%3A%20more%20%3A%20%20%5C%5C%20%20%3D%20ax%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7B2%7D%5E%7B2%7D%20%29)
but from general factorization:
![{ \boxed{( {a}^{2} + {b}^{2}) = {(a + b)}^{2} - 2ab }}](https://tex.z-dn.net/?f=%7B%20%5Cboxed%7B%28%20%7Ba%7D%5E%7B2%7D%20%2B%20%20%7Bb%7D%5E%7B2%7D%29%20%3D%20%20%7B%28a%20%2B%20b%29%7D%5E%7B2%7D%20%20%20-%202ab%20%7D%7D)
a » x
b » 2
therefore:
![= ax \{ {(x + 2)}^{2} - 2(x)(2) \} \\ \\ = { \boxed{ \boxed{ax( {x + 2)}^{2} - 4x }}}](https://tex.z-dn.net/?f=%20%3D%20ax%20%5C%7B%20%7B%28x%20%2B%202%29%7D%5E%7B2%7D%20%20-%202%28x%29%282%29%20%5C%7D%20%5C%5C%20%20%5C%5C%20%20%3D%20%7B%20%5Cboxed%7B%20%5Cboxed%7Bax%28%20%7Bx%20%2B%202%29%7D%5E%7B2%7D%20-%204x%20%7D%7D%7D)
Answer:
39
Step-by-step explanation:
multiply the 5 by 13 and get 65 and multiply thr 3 by 13 its 39
Answer:
subtracting 5 from both sides
Step-by-step explanation:
please mark brainliest lol :)
Answer:24 cards - 20%= 19.2
Step-by-step explanation: